Understanding the role of customer trust in e-commerce - Khan, Istiak; Mohamadali, Noor Azizah (AIRCC Publishing Corporation, 2023)
Trust is a big part of how well e-commerce works and it is also a big part of how people decide what to buy. As more and more business is done online, companies that want to build customer loyalty and involvement must understand the complex relationship between trust and e-commerce. This study paper looks at the many distinct aspects of trust in e-commerce and how it affects people’s actions. By looking at the various aspects and causes of trust and how to build and keep trust, this study shows how businesses can create a trustworthy online environment that makes customers happier and leads to long-term success.